High efficiency Doherty power amplifiers for modern wireless communication systems: A brief review - Mussa Mabrok; Zahriladha Zakaria; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Dueto the high peak to average power ratio (PAPR) of modern modulated signals, power amplifiers (PAs) have been forced to operate at the back-off (BO) region of their saturation power in order to avoid signal clipping and distortion. However, classical PAs suffer from low efficiency in the BO region operation. Therefore, efficiency has to be enhanced in that region. Many techniques have been proposed. Among them, the Doherty power amplifier (DPA) is considered as the most suitable technique due to its simple structure and high performance. However, its conventional design is limited to a 6 dB BO level, which does not satisfy the requirements of modern communication systems. In this paper, a brief review of the most significant techniques of high-efficiency DPA is presented. First, DPA topology and its operation principles are briefly discussed. Second, efficiency enhancement techniques such as an asymmetrical DPA, output combiner modification, gate bias adaption, offset line optimization, and multi-way DPA were discussed. The study shows that the most suitable, simple, and effective solution is an asymmetrical approach. However, it needs to be investigated in terms of bandwidth in order to meet the efficiency-bandwidth requirements of modern wireless communication systems such as 5G.